A novel reconfigurable autonomous mobile chassis: design, modelling, and simulation - Ji, Yuan (2025)
The increasing adoption of Autonomous Mobile Robots (AMRs) in industrial settings, such as warehouses and factories, has been driven by their ability to save labor and improve efficiency. In this paper, we propose a novel reconfigurable AMR design, which is capable of dynamically changing its width and length to accommodate the working space. The reconfigurable AMR has two main components, the corner module (CM) and the sliding module (SM), both of which the mechanical structures are built in MTALAB/Simscape. The six working modes, as well as the state machine for modes transition, are also defined therein. Furthermore, the reconfigurable AMR can proactively adjust its width and length based on actuators and external constraints, as determined by an adaptive dimensions optimization problem, thereby improving the anti-rollover, stability, and efficacy performance. The simulations under a typical warehouse scenario are also conducted in MTALAB/Simscape. The validation results indicate that the reconfigurable structure design is highly flexible and that the proposed optimization problem is feasible.